Family Foundations: adaptação e avaliação de um programa de intervenção em coparentalidade para casais em transição para a parentalidade - Guerra, Lívia Lira de Lima (2022)
During the transition to parenthood - the period between pregnancy and the baby’s first months of life - levels of depression, anxiety and marital conflict increase substantially, with negative results for all family members. This points to the importance of developing preventive programs. The overall objective of this study was to adapt, offer, and evaluate the effectiveness of the Family Foundations intervention program, focused on improving the coparenting relationship of couples during the transition to parenthood. The intervention is conducted in two phases, the prenatal phase, when the parents are still expecting their first child, and the postnatal phase, which begins when the baby is around three to six months old. In Study I, the 12 steps of the adaptation of the Family Foundations program are reported, to develop the Brazilian version of this program, called Famílias Fortalecidas. Strong evidence was found for the acceptability of the program. The other studies (II, III and IV) involve parts of the adaptation process. In Study II, to identify behaviors considered to be part of the coparenting relationship, a systematic review of the national and international literature on observational methods being used to evaluate coparenting was conducted, following the PRISMA methodological recommendations. Coparenting behaviors were evaluated in the prenatal period and with parents of children in various age groups. The components of the three most cited models of coparenting were sufficient for encompassing all the coparenting behaviors identified in these studies. In Study III, the aim was to identify coparenting skills used by Brazilian parents in their coparenting relationship. The participants were 31 fathers and mothers, 18 years of age or over, with a first child six years of age or under. A semi-structured interview script was used to ask about coparenting tasks, and the strategies used in this relationship. The transcripts were analyzed, using content analysis techniques, and the following categories were identified: (a) communication skills -- giving recognition or praise; (b) joint decision-making and conflict resolution skills: asking each other’s opinions before making a decision, and (c) bonding skills: expressing positive emotions, sharing positive experiences and enjoyment of child-related happenings using verbal expressions and non-verbal behaviors (such as smiling and exchanging glances). Finally, in Study IV, the objective was to analyze the effects of a brief, coparenting intervention program. This study had a quasi-experimental design, with an Intervention Group (n=24 couples) and a Comparison Group (n=14 couples). Participants included couples that were married or living together, expecting their first child together. The instruments used before and after the program, to evaluate the effects of the program were: the Dyadic Adjustment Scale (EAD), the Marital Social Skills Inventory (IHSC), the Conflict Tactics Scale (ETC), the Beck Depression Inventory (BDI-II), and the Parental Educational Competence Self-Assessment Questionnaire (QACEP). Four additional instruments were included in the post-test: the Coparental Relationship Scale (ERC), the Perceived Stress Scale, the Parental Burnout Assessment – BR, and the Child Temperament Questionnaire. The program was effective in improving the coparenting relationship and in reducing negative impacts on the marital relationship of couples participating in the Intervention Group, compared to those in the Comparison Group. As study limitations, the children may have been too young to observe effects of the program on participants’ perceptions of parental competence and on symptoms of depression. In addition, the greater drop-out rate in the Comparison Group (44%) than in the Intervention Group (20%) reduced the power of the analyses, affecting the possibility of obtaining results with statistical significance. However, the effect size of the differences indicate the importance of the program. To establish more robust evidence, in future studies it will be important to increase the number of couples in the Intervention and the Comparison Groups, and to monitor couples to assess the medium and long-term effects of the program, using additional measures of parenting and child behavior.